The role of matrix metalloproteinase-9 in cardiac remodeling and dysfunction and as a possible blood biomarker in heart failure - Keuri Eleutério Rodrigues; Maria Helena Barbosa Pontes; Manoel Benedito Sousa Cantão; Alejandro Ferraz Prado (Elsevier, 2024)
Heart failure (HF) is the leading cause of morbidity and mortality in cardiovascular diseases, being responsible for many hospitalizations annually. HF is considered a public health problem with significant economic and social impact, which makes searches essential for strategies that improve the ability to predict and diagnose HF. In this way, biomarkers can help in risk stratification for a more personalized approach to patients with HF. Preclinical and clinical evidence shows the participation of matrix metalloproteinase 9 (MMP-9) in the HF process. In this review, we will demonstrate the critical role that MMP-9 plays in cardiac remodeling and dysfunction. We will also show its importance as a blood biomarker in acute and chronic HF patients.